2017
DOI: 10.15366/reice2017.15.4.001
|View full text |Cite
|
Sign up to set email alerts
|

School Climate in Highly Effective Schools in the Autonomous Region of the Basque Country (Spain)

Abstract: This study, part of a wider study, presents the results concerning school climate as examples of best practices in highly effective schools. Thirty-two primary and secondary schools were identified and selected using multilevel statistical modelling techniques and hierarchical linear models that identified schools with higher-than-expected student results from among all the schools in the Autonomous Region of the Basque Country. Once schools had been identified and characterised, the best practices were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
1
9
0
3
Order By: Relevance
“…Based on hypothesis testing with a path coefficient of p54 = 0.685. The research results obtained also support the research conducted by Maxwell et al [33]; Tubbs and Mary [34]; Etxeberria [13]; Brault, Michel, and Asabelle [35]; and Kwong [14] that school culture has a significant effect on the performance of childfriendly schools. School culture can be seen from the orientation of school program results.…”
Section: School Culture On Child-friendly School Performancesupporting
confidence: 85%
See 1 more Smart Citation
“…Based on hypothesis testing with a path coefficient of p54 = 0.685. The research results obtained also support the research conducted by Maxwell et al [33]; Tubbs and Mary [34]; Etxeberria [13]; Brault, Michel, and Asabelle [35]; and Kwong [14] that school culture has a significant effect on the performance of childfriendly schools. School culture can be seen from the orientation of school program results.…”
Section: School Culture On Child-friendly School Performancesupporting
confidence: 85%
“…Efforts to develop a school culture that is oriented towards achieving the performance of Child-friendly Schools, school principals can organize and maintain in such a way the continuity of activities in schools. The relationship of school culture variables to the performance of Child-friendly Schools is shown in the research of Etxeberria [13] which states that school culture is related to teacher commitment to educational work, involvement, teamwork, and participatory school management in the Basque Autonomous Region of Spain. The results suggest to expand our understanding of culture beyond peaceful coexistence between students, and to include processes of teamwork and democratic participation in plans for peaceful coexistence.…”
Section: Marks and Susanmentioning
confidence: 99%
“…Estos resultados contrastan con otros que han encontrado predicción de la victimización de adolescentes a partir de variables del clima escolar. https://doi.org/10.15359/ree.26-3.11 https://www.revistas.una.ac.cr/index.php/educare educare@una.ac.cr De acuerdo con Etxeberria et al (2017), un clima escolar favorable es percibido por el estudiantado como un factor para el buen funcionamiento de la escuela, pero además las variables de convivencia escolar son importantes, debido a que en otros estudios se ha evidenciado que explican en un porcentaje considerable el rendimiento académico (Cerda et al, 2018).…”
Section: Discusión Y Conclusionesunclassified
“…These; leadership, high expectations, rules and discipline, mission focus, monitoring process (assessment and evaluation), positive / supportive climate, time emphasis on duty, parent/community participation, staff development, basic skills, teacher participation in decisions, grouping procedures, teacher quality and other elements. Etxeberria, Intxausti and Azpillaga (2017), in their study, reported that high-impact schools in general have teachers live together in a safe, peaceful and conflict-free environment of the school community with a set of democratic rules, conflict resolution attitudes characterized by reconciliation and agreement, and a sense of mutual support of the teacher-management team, and that each school has agreed on its own vision. In summary, they have a good / positive climate.…”
Section: Introductionmentioning
confidence: 99%
“…They emphasized the importance of having a stable team of teachers in order to create a positive/good climate. Although different characteristics have been proposed as to the characteristics of effective schools, many researchers agree on the "school climate" characteristics (Doran, 2004;Etxeberria, Intxausti, & Azpillaga, 2017;Scheerens, & Creemers, 1989;Şişman, 1996;Turhan, Şener, & Gündüzalp, 2017;Uline, Miller, & Tschannen-Moran, 1998;Whetten & Cameron, 1984). In other words, effective schools, administrators, teachers and other employees have a climate that believes that all students can learn and reflects this on their behavior (Lezotte 1991).…”
Section: Introductionmentioning
confidence: 99%